Real-world optimization of tunnel lengths in tunneled peripherally inserted central catheters for cancer patients: A multi-center retrospective cohort study - Yinyin Wu; Wei Ding; Yuying Liu; Qianhong Deng; Fengqin Tao; Hanbin Chen; Chang Chen; Meng Xiao; Bilong Feng (PLoS ONE, 2025)
Background Standardized guidelines for optimal tunnel length in tunneled peripherally inserted central catheters (PICCs) are lacking. Objectives The objective of this study was to evaluate the real-world impact of tunnel length on clinical outcomes. Methods This retrospective cohort study included 207 cancer patients who received tunneled PICCs, categorized into a control group (tunnel length > 4 cm, n = 134) and an observation group (tunnel length ≤ 4 cm, n = 73). Propensity score matching (PSM) was used to address baseline heterogeneity. Cox regression analyses were used to assess the risk of complication during a 120-day follow-up. Results Compared to the control group (tunnel length > 4 cm), the observation group (tunnel length ≤ 4 cm) had a significantly higher adjusted overall complication risk (HR = 2.92, 95% CI: 1.07–7.94, P = 0.036) and unplanned catheter removal rate (4.4% vs. 0.0%, P = 0.027), confirming the safety of longer tunnels despite comparable comfort levels between groups. After PSM, Cox regression analysis showed results consistent with those from the unmatched cohort. Subgroup analyses revealed a reduced risk of complications with longer tunnels in patients with BMI ≤ 25 kg/m² (HR = 0.29, 95% CI: 0.11–0.82), without hypertension (HR = 0.36, 95% CI: 0.13–1.00), without diabetes (HR = 0.38, 95% CI: 0.15–0.97), and with solid tumors (HR = 0.31, 95% CI: 0.11–0.85). Conclusion The results show that tunnel lengths > 4 cm reduce overall complications and prolong catheter retention, supporting the implementation of standardized protocols while advocating for personalized adjustments based on BMI, comorbidities, and cancer type.